2012
DOI: 10.1366/12-06611
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Fourier Transform Infrared (FT-IR) Spectroscopy and X-ray Diffraction (XRD) in the Determination of Cotton Fiber Crystallinity

Abstract: Despite considerable efforts in developing curve-fitting protocols to evaluate the crystallinity index (CI) from X-ray diffraction (XRD) measurements, in its present state XRD can only provide a qualitative or semi-quantitative assessment of the amounts of crystalline or amorphous fraction in a sample. The greatest barrier to establishing quantitative XRD is the lack of appropriate cellulose standards, which are needed to calibrate the XRD measurements. In practice, samples with known CI are very difficult to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 18 publications
(38 reference statements)
3
76
0
Order By: Relevance
“…The wet mass of BC can be 100-200 times Unauthenticated Download Date | 5/10/18 9:38 AM related to the increase in the content of crystalline form and the decrease in amorphous state in cellulose. This is consistent with previous reports from Liu et al 40 who reported that plant cellulose had a different ATR-FTIR profi le depending on its age. The observed differences in BC molecular structure can be also explained by the drop in the values of the average degree of polymerization and may indicate changes in the size of crystallites over the time of BC synthesis.…”
Section: Resultssupporting
confidence: 93%
“…The wet mass of BC can be 100-200 times Unauthenticated Download Date | 5/10/18 9:38 AM related to the increase in the content of crystalline form and the decrease in amorphous state in cellulose. This is consistent with previous reports from Liu et al 40 who reported that plant cellulose had a different ATR-FTIR profi le depending on its age. The observed differences in BC molecular structure can be also explained by the drop in the values of the average degree of polymerization and may indicate changes in the size of crystallites over the time of BC synthesis.…”
Section: Resultssupporting
confidence: 93%
“…It might result from the presence of C-O stretching mode of primary alcohols (-C6H2-O6H), in which band at 968 cm −1 is characteristic for BC with a high degree of crystallinity, whereas the signal at 1042 cm −1 corresponds to the amorphous form of cellulose. The analyzed spectra showed also the intense cross-peaks observed outside the diagonal axis referring to the above-mentioned signals and indicating that there have been changes in crystallinity in these regions [43].…”
Section: Analysis Of Atr-ftir Spectramentioning
confidence: 82%
“…The ATR-FTIR spectra of BC were analyzed by means of the two-dimensional correlation (2D correlation) analysis using 2Dshige software (Shigeaki Morita, Kwansei-Gakuin University, Nishinomiya, Japan). For the 2D correlation analysis, the areas of the spectra were restricted to the range between 1800 cm −1 and 650 cm −1 , normalized at the frequency band of 660 cm −1 using the methodology described by Liu et al [42,43] and analyzed using Origin Pro 8 software.…”
Section: Attenuated Total Reflectance Fourier Transform Infrared Specmentioning
confidence: 99%
“…The dataset was then loaded into Microsoft Excel 2000 to calculate the CI IR parameter using the same algorithms previously reported [19,20]. Representative and baseline-uncorrected ATR-FTIR spectra in the 1800 to 600 cm …”
Section: Ir Calculationmentioning
confidence: 99%
“…It has been determined predominantly by a curve-fitting process that extracts individual crystalline peaks from the XRD intensity profile. As a different approach, ATR-FTIR spectroscopy technique was attempted to identify the spectral intensity differences between immature and mature fibers and further to estimate the degree of cotton cellulose maturity (M IR ) and cotton fiber crystallinity (CI IR ) [19,20]. It concluded that using the ATR-FTIR method to assess the cotton fiber CI is appropriate and reasonable with the following considerations: (1) a simple ATR-FTIR protocol avoids the need to perform any pretreatment of the cotton fibers (such as cutting in a routine XRD measurement); (2) it can analyze small amounts of fiber (as little as 0.5 mg) compared to ~150 mg fibers on an XRD aluminum holder (25 mm diameter × 2 mm deep); and (3) it requires only a short time (less than 2 min) for sample loading, spectral acquisition, and subsequent result reporting.…”
Section: Introductionmentioning
confidence: 99%